(untitled) (International Journal of Applied Research in Management and Economics, 2020)
This research is important because there are still many batik craftsmen unconsciousness of the importance of product quality and brand image in influencing the possibility of consumers buying products (batik Lasem cloth). Batik Lasem is a traditional Indonesian cloth originating from the City of Lasem in Central Java, Indonesia. The purpose of this research is to empirically examine product quality concepts consisting of eight (8) dimensions (performance, reliability, features, suitability, durability, service capability, aesthetics, and quality of customer perception) and brand image with a willingness to buy. The data collection was done involving 181 Lasem batik buyers in Central Java, Indonesia. Data were analyzed using SPSS version 20. Three (3) hypotheses in this study were accepted. The result of the analysis shows that 1). There is a positive significant relationship between product quality and willingness to buy; 2) There is a positive significant relationship between brand image and willingness to buy, and 3). There is a significant relationship between product quality and brand image with willingness to buy.